The Viswanathan Dilemma at Little, Brown, Publishers. - Emblidge, David (International Journal of the Humanities, 2007)
In spring 2006 a Harvard university student, Ms. Viswanathan, is caught plagiarizing in her already published young adult novel, causing consternation for the author, her agent, her ghost book doctor, her publisher and for booksellers. What should the publisher do? The case poses difficult problems in the areas of business ethics as applied to creative writing and publishing. Are there any excuses for plagiarism when the author claims she has a photographic memory that runs out of control? Can the editors be held responsible for not catching the rampant plagiarism in the manuscript? Are there any good options for the publisher who has invested substantial amounts of money in this budding author's new career and has hopes for a film rights sale in the near future? Should bookstores continue to sell the book? Do consumers have any role in resolving these ethical dilemmas, or is the book buyer free to read anything, even if its content is contaminated by plagiarism?